NAVKIDS2 trial: a multi-centre, waitlisted randomised controlled trial of a patient navigator intervention in children with chronic kidney disease — statistical analysis plan and update to the protocol - Anita van Zwieten; Elizabeth G. Ryan; Patrina Caldwell; Kirsten Howard; Allison Tong; Jonathan C. Craig; Stephen I. Alexander; Martin Howell; Armando Teixeira-Pinto; Carmel M. Hawley; Shilpanjali Jesudason; Amanda Walker; et al. (Trials, 2022)
Abstract Background This update summarises key changes made to the protocol since the publication of the original protocol for the NAVKIDS 2 trial of patient navigators for children with chronic kidney disease (CKD) experiencing social disadvantage and provides the statistical analysis plan (SAP) which has not previously been published. Methods/design The original protocol was published in BMC Nephrology ( https://doi.org/10.1186/s12882-019-1325-y ) prior to the commencement of trial recruitment. During the course of the trial, some key methodological changes needed to be made including changes to eligibility criteria (addition of patients with CKD stages 1–2, broadening of financial status eligibility criterion, addition of patients living in rural/remote areas, modification of age eligibility to 0–16 years, addition of limits related to the language spoken by family, guidance regarding families with multiple eligible children), changes to sites, reduction of sample size, addition of virtual options for consent and study procedures in response to the COVID-19 pandemic, removal of staggered recruitment across sites, addition of outcomes, and changes to the timing and number of assessments. This update summarises the changes made and their rationale and provides the detailed plan for statistical analysis of the trial. These changes have been finalised prior to the completion of study follow-up and the commencement of data analysis. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12618001152213 . Prospectively registered on 12 July 2018